MENINGKATKAN KEMAMPUAN MENGENAL BILANGAN MELALUI MEDIA POHON HITUNG FLANEL PADA ANAK USIA 4-5 TAHUN - Latifah, Nur; Supriyatno, Arie; Laely, Khusnul (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2015)
The purpose of this study to determine the ability to know the numbers determine the increase through media flannel tree count in children aged 4-5 years.This study is a class action, in which each cycle consists of four steps: planning, execution, observation and evaluation. Research subjects in this study were students in group A in the ABA TK Tempuran Magelang totaling 19 children. Variables used include input variables (ability to know the number is low), the process variables (learning to use the media tree count flannel) and output variables (the ability to know a high number). Data collection methods used in this research is the method of observation, interviews and documentation. The research instrument used was the observation sheet and interview guides. Data analysis techniques used in this action research is descriptive quantitative data analysis techniques.The research proves that the media tree flannel count numbers can improve cognitive ability in children aged 4-5 years Tempuran ABA TK. Results of preliminary observations note that the average achievement of the ability to know the number of new subjects stood at 62.4%, still far from the target to be achieved is 75%. After learning activities using the media tree flannel count in the first cycle, the average achievement of the ability to know the subject number increased to 85.2%.